2002
DOI: 10.1097/00006123-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellopontine Angle Epidermoids Presenting with Cranial Nerve Hyperactive Dysfunction: Pathogenesis and Long-term Surgical Results in 30 Patients

Abstract: Hyperactive dysfunction of the cranial nerves, especially TN, may be the initial and only symptom that patients with cerebellopontine angle epidermoids experience. The occurrence of TN at a younger age was characteristic of TN patients with epidermoids, in contrast to patients with TN due to a vascular cause. The symptom is elicited by compression of the nerve by the tumor per se, by an artery that is displaced to the nerve, or by both. Careful resection of the tumor, whose capsule occasionally is strongly adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(163 citation statements)
references
References 46 publications
5
148
0
10
Order By: Relevance
“…Se presentan a nivel del ángulo pontocerebeloso, de la región paraselar y cuadrigeminal 2,15,21 . También se han descrito casos en otras localizaciones menos frecuentes, como en la Cisura de Silvio, región quiasmática, a nivel ventricular 6 16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Se presentan a nivel del ángulo pontocerebeloso, de la región paraselar y cuadrigeminal 2,15,21 . También se han descrito casos en otras localizaciones menos frecuentes, como en la Cisura de Silvio, región quiasmática, a nivel ventricular 6 16 .…”
Section: Discussionunclassified
“…Clínicamente se pueden manifestar por alteración de pares craneales 15 o síndrome cerebeloso a nivel infratentorial. Los QE supratentoriales se presentan por cefaleas, crisis comiciales, déficit motores o sensitivos y/o hidrocefalia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…They include vascular compression, tumors in the CPA, extracranial lesions, and unknown etiology 15,17) . GPN caused by a CPA tumor has been previously reported; however, it is very rare 13,17) . In the report on combined hyperactive dysfunction syndrome of the cranial nerves, Kobata et al 14) reported three cases of epidermoid tumors located in the CPA as a causative factor of the syndrome, but GPN was not present in those cases.…”
Section: A B Cmentioning
confidence: 99%
“…[2][3][4][5] This study was done to identify and evaluate neurovascular and tumor interrelations in 14 patients with symptomatic (secondary) TN caused by CPA tumors. In this article 10 years of clinical experience in management of patients with TN secondary to CPA tumors is summarized.…”
mentioning
confidence: 99%